Long-term effect of sitagliptin on endothelial function in type 2 diabetes: a sub-analysis of the PROLOGUE study. Issue 1 (December 2016) - Maruhashi, Tatsuya; Higashi, Yukihito; Kihara, Yasuki; Yamada, Hirotsugu; Sata, Masataka; Ueda, Shinichiro; Odawara, Masato; Terauchi, Yasuo; Dai, Kazuoki; Ohno, Jun; Iida, Masato; Sano, Hiroaki; et al.
Abstract Background As a sub-analysis of the PROLOGUE study, we evaluated the long-term effect of sitagliptin, a dipeptidyl peptidase 4 inhibitor, on endothelial function in the conduit brachial artery in patients with type 2 diabetes. Methods In the PROLOGUE study, patients were randomly assigned to either add-on sitagliptin treatment (sitagliptin group) or continued conventional antihyperglycemic treatment (conventional group). Among the 463 participants in the PROLOGUE study, FMD was measured in 17 patients in the sitagliptin group and 18 patients in the conventional group at the beginning and after 12 and 24 months of treatment. Results HbA1c levels were significantly decreased after 12 and 24 months of treatment compared to baseline values in both groups (7.0 ± 0.4 vs. 6.6 ± 0.3 and 6.6 ± 0.4 % in the sitagliptin group; 7.0 ± 0.6 vs. 6.6 ± 0.7 and 6.6 ± 0.7 % in the conventional group; P < 0.05, respectively). There was no significant difference between FMD values at baseline and after 12 and 24 months in the sitagliptin group (4.3 ± 2.6 vs. 4.4 ± 2.1 and 4.4 ± 2.3 %, P = 1.0, respectively). Although FMD had a tendency to increase from 4.3 ± 2.4 % at baseline to 5.2 ± 1.9 % after 12 months and 5.1 ± 2.2 % after 24 months in the conventional group, there was no significant difference between FMD values at baseline and after 12 and 24 months (P = 0.36 and 0.33, respectively). Conclusions Add-on sitagliptin to conventional antihyperglycemic drugs in patients with type 2 diabetes did not alter endothelial function in the conduit brachial artery measured by FMD during a 2-year study period. Sitagliptin may be used without concern for an adverse effect on endothelial function in patients with type 2 diabetes. Trial registration: University hospital Medical Information Network (UMIN) Center: ID UMIN000004490